COLLABORATIVE STORYTELLING WORKSHOP FOR STUDENTS IN CANBERRA: LEARNING INDONESIAN CULTURE THROUGH LUTUNG KASARUNG FOLKTALE - Eva Leiliyanti; Haniyatuz Zaidah Salma; Clayrine Devany; Miftahulkhairah Anwar; Leonie Harwood (JMM (Jurnal Masyarakat Mandiri), 2024)
Abstrak: Penurunan kompetensi dalam pelajaran Bahasa Indonesia di Australia menjadi perhatian dalam kerangka kerja sama bilateral di bidang pendidikan antara Indonesia dan Australia. Penelitian ini bertujuan untuk meningkatkan kompetensi bahasa dan budaya Indonesia pada siswa di dua sekolah di Canberra, yaitu Burgmann Anglican School dan Trinity Christian School, melalui lokakarya kolaboratif. Lokakarya ini melibatkan 112 siswa kelas 3-5 di Burgmann Anglican School dan 310 siswa kelas 6-8 di Trinity Christian School. Diselenggarakan oleh empat program studi dari Universitas Negeri Jakarta—S1 Bahasa dan Sastra Indonesia, S1 Sastra Inggris, S1 Pendidikan Bahasa Inggris, dan S1 Pendidikan Seni Tari—serta Program Studi S2 Pendidikan Bahasa Indonesia, lokakarya ini menekankan pada pembelajaran interaktif melalui multimedia, lokakarya tari, serta permainan edukatif dengan tema cerita rakyat "Lutung Kasarung." Tujuan utamanya adalah untuk meningkatkan kemampuan berbahasa Indonesia dan minat siswa dalam mempelajari bahasa serta budaya Indonesia. Evaluasi melalui survei menunjukkan peningkatan signifikan dalam kompetensi bahasa Indonesia dan pemahaman lintas budaya. Hasil ini menggarisbawahi pentingnya pendekatan pendidikan berbasis budaya dalam memperkuat hubungan bilateral dan pelestarian bahasa di tingkat sekolah dasar. Abstract: Declining competence in Indonesian language learning in Australia is a concern within the framework of bilateral cooperation in education between Indonesia and Australia. This study aimed to improve Indonesian language and cultural competence in students at two schools in Canberra, Burgmann Anglican School and Trinity Christian School, through collaborative workshops. The workshops involved 112 students in grades 3-5 at Burgmann Anglican School and 310 students in grades 6-8 at Trinity Christian School. Organised by four study programmes from Universitas Negeri Jakarta - Bachelor of Indonesian Language and Literature, Bachelor of English Literature, Bachelor of English Language Education, and Bachelor of Dance Education - as well as the Master of Indonesian Language Education Study Programme, the workshop emphasised interactive learning through multimedia, dance workshops, and educational games with the folklore theme of ‘Lutung Kasarung’. The main objective was to improve students' Indonesian language skills and interest in learning Indonesian language and culture. Evaluation through surveys showed significant improvements in Indonesian language competence and cross-cultural understanding. These results underscore the importance of a culture-based education approach in strengthening bilateral relations and language preservation at the primary school level.